iTRAQ-based proteomic study on monocyte cell model discovered an association of LAMP2 downregulation with HIV-1 latency - Lin Yin; Qimin Wang; Siyuan Liu; Jun Chen; Yujiao Zhang; Lingqing Lu; Hongzhou Lu; Zhigang Song; Lijun Zhang (Proteome Science, 2024)
Abstract Background Patients with immunodeficiency virus-1 (HIV-1) infection are challenging to be cured completely due to the existence of HIV-1 latency reservoirs. However, the knowledge of the mechanisms and biomarkers associated with HIV-1 latency is limited. Therefore, identifying proteins related to HIV-1 latency could provide new insights into the underlying mechanisms of HIV-1 latency, and ultimately contribute to the eradication of HIV reservoirs. Methods An Isobaric Tags for Relative and Absolute Quantification (iTRAQ)-labeled subcellular proteomic study was performed on an HIV-1 latently infected cell model (U1, a HIV-1-integrated U937 cell line) and its control (U937). Differentially expressed proteins (DEPs) were analyzed using STRING-DB. Selected DEPs were further evaluated by western blotting and multiple reaction monitoring technology in both cell model and patient-derived cluster of differentiation 4 (CD4)+ T cells. Finally, we investigated the relationship between a specific DEP lysosome-associated membrane glycoprotein 2 (LAMP2) and HIV-1 reactivation by panobinostat or lysosome regulation by a lysosomotropic agent hydroxychloroquine in U1 and U937 cells. Results In total, 110 DEPs were identified in U1 cells comparing to U937 control cells. Bioinformatics analysis suggested associations of the altered proteins with the immune response and endosomal/lysosomal pathway. LAMP2, leukocyte surface antigen CD47, CD55, and ITGA6 were downregulated in HIV-1 latent cells. Downregulated LAMP2 was further confirmed in resting CD4+ T cells from patients with latent HIV-1 infection. Furthermore, both HIV-1 reactivation by panobinostat and stimulation with hydroxychloroquine upregulated LAMP2 expression. Conclusions Our results indicated the involvement of the endosomal/lysosomal pathway in HIV-1 latency in macrophage cell model. The down-modulation of LAMP2 was associated with HIV latency, and the restoration of LAMP2 expression accompanied the transition of viral latency to active infection. This study provides new insights into the mechanism of HIV-1 latency and potential strategies for eradicating HIV-1 reservoirs by targeting LAMP2 expression.